2018
DOI: 10.1002/lary.27424
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone telemedical emergency department consults for screening of nonacute dizziness

Abstract: Objectives/Hypothesis Each year, the United States spends over $4 billion on emergency department visits for evaluation of dizziness. Benign paroxysmal positional vertigo (BPPV) is a common cause of dizziness that can easily be diagnosed by observing characteristic eye movements during the Dix‐Hallpike test (DHT). The DHT is easily performed; however, interpretation requires more advanced training. This may be part of the reason it is not commonly performed in emergency departments, and instead, patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…[28][29][30] The WHO also recommends the use of information and communication technology to maintain and improve health, so-called e-Health. 31 In the ENT field related to vertigo/dizziness, online medicine may include video-lectured diagnosis and canalith repositioning treatment for BPPV, 32 stress less life guidance for MD, and vestibular rehabilitation for VN and SDV. After the COVID-19 pandemic ends, it will be time to prepare for an advanced way of providing medical care, not only for the disease itself but also for the mental distress behind persistent symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] The WHO also recommends the use of information and communication technology to maintain and improve health, so-called e-Health. 31 In the ENT field related to vertigo/dizziness, online medicine may include video-lectured diagnosis and canalith repositioning treatment for BPPV, 32 stress less life guidance for MD, and vestibular rehabilitation for VN and SDV. After the COVID-19 pandemic ends, it will be time to prepare for an advanced way of providing medical care, not only for the disease itself but also for the mental distress behind persistent symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the images obtained by this portable equipment were satisfactory and useful to the diagnosis process. 22 A research on health care was conducted in a resourcerestricted, post-Katrina Hurricane South Louisiana. The authors claimed that telemedicine was a viable delivery model for neurotology care.…”
Section: Resultsmentioning
confidence: 99%
“…The search for the terms "telemedicine AND (dizziness OR vertigo)" returned 25 articles in the PubMed database. Three addressed the applications of telemedicine in the diagnosis of vestibular and balance disorders 36,37,38,39 . Thus, we note that research in this area is still very scarce.…”
Section: Vestibular Disordersmentioning
confidence: 99%
“…Regarding recurrent vertigo, a study with 37 patients evaluated the use of a video of the patient's eyes during the Dix-Hallpike maneuver, recorded by smartphone, in the diagnosis of vestibular disorders 36 . Seven patients were diagnosed with BPPV, the sensitivity of the method for this diagnosis being 92.86% and the specificity 100%.…”
Section: Vestibular Disordersmentioning
confidence: 99%